Syntactic Awareness of Early Childhood Aged 5-6: A Case of Sentence Structure - Maghfira Zhafirni (Passage, 2018)
This study seeks to examine syntactic awareness of children aged 5-6 in Indonesian context. The aims of the study is to investigate early childhood in identifying and correcting active and passive sentences and then describing the characteristics of high and low performing students. This study employs a descriptive qualitative approach to data collection and analysis. The data were collected in three ways: 1) Assesment tests, 2) Questionnaire, and 3) Interview. The analysis reveals that the children could identify and correct active sentences (76.69%) and passive sentences (67.16%). In describing the quantitative analysis, this study focuses on the high and low performing students in revealing the characteristics of the data. This study suggests that children have their capacity to engage in learning linguistic. Therefore, the result of this study could be considered to be the cases for further literacy learning. Based on the social aspects, there are 3 main social aspects that characterize high and low performing students; parents’ education background, children activity, and the quantity of child-directed speech. Keywords: syntactic awareness, active and passive sentence, kindergarten stude